Comparative functional analysis of macrophage phagocytosis in Dagu chickens and Wenchang chickens - Zhang, Jin; Wang, Qiao; Li, Qinghe; Wang, Zixuan; Zheng, Maiqing; Wen, Jie; Zhao, Guiping (Frontiers in Immunology, 2023)
Phagocytosis of macrophages constitutes a powerful barrier to innate immunity. Differences in the phagocytic function of macrophages among chicken breeds have rarely been reported, and the molecular mechanisms underlying phagocytosis remain poorly understood. This study compared functional difference of macrophages in Dagu chickens, originated in Zhuanghe, Liaoning Province, China, and Wenchang chickens, originated from Hainan Island in the South China Sea, and explored the potential molecular mechanisms by integrated analysis of mRNA expression profiles of macrophages and whole genome sequencing. Immunological parameters in peripheral blood indicated that Dagu chickens were more resistant to Salmonella challenge at 28 days old. Phagocytosis index and phagocytosis rate of macrophages displayed Dagu chickens performed a significantly higher phagocytic ability of macrophages at 14 and 28 days old. Furthermore, comparative analysis of mRNA expression profiles of macrophages of two breeds at 28 days old revealed that 1136 differentially expressed genes (DEGs), and 22 DEGs (e.g., H2AFZ, SNRPA1, CUEDC2, S100A12) were found to be hub genes regulating phagocytosis by participating in different immunological biological signaling pathways. In addition, many DEGs and hub genes were under strong differentiation in genome between two breeds, the H2AFZ gene was an intersection of DEGs and hub genes. These results provided a comprehensive functional comparison and transcriptomic profiles of macrophages in Chinese native chicken breeds, and deepened our understanding of the genetic mechanism of innate immunity.